Wakaf di Indonesia: (Kajian Historis Yuridis) - Midh, Fredy G (Institut Agama Islam Negeri Metro, 2022)
Waqf is an integral aspect of Islamic teachings with a direct social impact. It is part of muamalah (Islamic transactions) and has been carefully regulated in Islamic law. Over time, waqf has evolved from being limited to immovable properties such as land and buildings to include cash waqf, productive waqf, services, and other forms. This study is a normative juridical analysis, employing a descriptive approach with deductive reasoning and qualitative analysis. The issues of fiqh muamalah pertain to legal studies that evolve within society, as fiqh and law are dynamic, adapting to changing times, places, and circumstances. The study highlights that waqf, as an act of worship, is based on the hope of earning Allah's pleasure, while from a shariah perspective, it is a mechanism to provide continuous benefits to the community through movable or immovable assets. In Indonesia, the development of waqf continues to align with global innovations and normative regulations, including those governing productive waqf. Given its strategic position, waqf has attracted significant attention from both society and the government. This paper explores the ongoing development and normative regulations surrounding waqf in Indonesia, emphasizing its potential for contributing to societal welfare.